ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERPANGKATAN DAN BENTUK AKAR DITINJAU DARI MINAT BELAJAR SISWA KELAS IX DI SMPS KRISTEN BNKP TELUKDALAM TA. 2022/2023 - Sarumaha, Wina Frederika (Universitas Nias Raya, 2023)
The problem of this research is the ability of students' mathematical problem solving which is influenced by interest in learning. The aims of this study were 1) to see how well students could apply problem-solving skills, 2) to see students' learning interests and 3) to understand what obstacles students experienced in working on problem-solving ability tests. This research uses a qualitative approach and applies descriptive research. The subjects in this study were 22 students in class VIII of Christian Private Middle School BNKP Telukdalam 2022/2023 Academic Year. There are three research instruments used, namely tests of students' problem solving abilities, questionnaires of student interest in learning and interviews. Data analysis techniques according to Miles and Huberman. The results showed that the students' abilities in terms of exponentials and root forms were sufficient, where there were 17 students who were in the sufficient category and 5 in the insufficient category. The results of the analysis of students' interest in learning were 2 students with high learning interest, 14 students with moderate learning interest and 6 students with low learning interest. So it can be concluded that students' problem-solving abilities are still quite sufficient and students' learning interest is in the medium category. So the suggestions put forward by researchers are 1) it is hoped that students often practice problem solving skills and increase their interest in learning mathematics, 2) Teachers are more aware of the challenges facing students.